Task adherence: an agentic perspective on task-focused dedication in an interrupting work environment. Issue 3 (10th June 2021) - Skousen, Tanner; Ames, Justin; Gaskin, James
Abstract : Purpose: Knowledge workers live and work in a technology-enabled, push-notification world full of interruptions that create information overload, often requiring these workers to utilize task switching as a mechanism to meet multiple competing tasks' demands. Previous research has examined both the positive and, more often, negative effects from interruptions and task switching on knowledge workers' performance. However, this paper aims to examine knowledge workers' agentic approach to managing interruption signals and consequent task switching to remain dedicated to the task at hand. Design/methodology/approach: Using an inductive grounded theory approach, we analyzed data from semi-structured interviews with knowledge workers regarding their experiences with task management strategies in interruption-heavy environments. Findings: The results indicate the emergence of a new construct that we define as "task adherence." We identified behavioral and technological mechanisms that knowledge workers employ to adhere to tasks, and we also categorized a host of environmental, personal and task-related factors that influence a knowledge worker's task adherence level. Practical implications: This study offers a novel conceptualization of key determinants of knowledge workers' task management. Through insights into how knowledge workers purposefully prepare for and address potential interruption signals, as well as manage task switching from subsequent interruptions, managers may be able to design new work processes to improve task performance. Originality/value: In a world of interruptions, task adherence adds to and clarifies a missing element in the time and task management dilemma that can enhance future efforts in designing strategies that enable knowledge workers to be more productive.